Implementasi Pemanfaatan Biogas Sebagai Energi Pendingin Susu Di Kecamatan Cepogo Kabupaten Boyolali - munahar, suroto; Purnomo, Bagiyo Condro; Widiyanto, Andi (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2019)
Central Java Province is a province that has dairy producing areas, including Boyolali Regency. This area is known as a dairy producing area that can supply milk needs in the Semarang, Klaten and Solo regions. However, the milk processing industry has not fully supported the dairy farmers. This condition can be known when the milk processing industry sets too high quality standards, causing problems for dairy farmers. This effect causes milk from dairy farmers to be thrown away. Another problem arises due to the inaccurate time of collection with the time of milk extraction to be accommodated in the KUD. Milk storage and cooling equipment owned by cattle farmers are not optimal because they use electricity sourced from PLN, thus increasing production costs. For that reason, in solving these problems by making milk storage devices and coolers with energi from biogas. The results of the implementation of this technology can reduce production costs because the milk storage process does not require energi from PLN. Besides, it can reduce milk wasted due to wrong timing of milk collection and order.